Molokh . Moloch - Sokurov, Aleksandr (Lenfilm, 1999)
Duration: 02:04:00 In 1942, in Bavaria, Eva Braun is alone, when Adolf Hitler arrives with Dr. Josef Goebbels and his wife Magda Goebbels and Martin Bormann to spend a couple of days without talking politics. Shot partially in the original fortress at Hitler's retreat in the Bavarian Alps, Sokurov's film blends surreal melodrama with archival footage, and functions as a fascinating inquiry into historical representation. Winner for Best Screenplay at the Cannes Film Festival.